1995
DOI: 10.1136/bmj.311.7010.899
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy in non-small cell lung cancer: a meta-analysis using updated data on individual patients from 52 randomised clinical trials

Abstract: Objective: To evaluate the effect of cytotoxic chemotherapy on survival in patients with non-small cell lung cancer. Design: Meta-analysis using updated data on individual patients from all available randomised trials, both published and unpublished. Subjects: 9387 patients (7151 deaths) from 52 randomised clinical trials. Main outcome measure: Survival. Results: The results for modern regimens containing cisplatin favoured chemotherapy in all comparisons and reached conventional levels of significance when us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
1
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 2,785 publications
(65 citation statements)
references
References 40 publications
0
62
1
2
Order By: Relevance
“…Meta-analysis of the randomized trials of adjuvant therapy of NSCLC in 1995 suggested the survival benefit of cisplatin-based chemotherapy after surgery [4]. From the meta-analysis using 9387 patients (7151 deaths) from 52 randomized clinical trials, trials comparing surgery with surgery plus chemotherapy gave a hazard ratio of 0.87 (13% reduction in the risk of death, equivalent to an absolute benefit of 5% at five years).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Meta-analysis of the randomized trials of adjuvant therapy of NSCLC in 1995 suggested the survival benefit of cisplatin-based chemotherapy after surgery [4]. From the meta-analysis using 9387 patients (7151 deaths) from 52 randomized clinical trials, trials comparing surgery with surgery plus chemotherapy gave a hazard ratio of 0.87 (13% reduction in the risk of death, equivalent to an absolute benefit of 5% at five years).…”
Section: Discussionmentioning
confidence: 99%
“…From the meta-analysis using 9387 patients (7151 deaths) from 52 randomized clinical trials, trials comparing surgery with surgery plus chemotherapy gave a hazard ratio of 0.87 (13% reduction in the risk of death, equivalent to an absolute benefit of 5% at five years). However, there are no statistical differences between the postoperative adjuvant group and surgery alone [4], and this includes a number of small trials and trials with the following disability criteria and chemotherapy regimens. After the above-mentioned meta-analysis by the Nonsmall Cell Lung Cancer Collaborative Group, several clinical trials examining the adjuvant chemotherapy were performed, but the efficacy of adjuvant chemotherapy remained a matter of controversy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination modality chemotherapy and radiotherapy conferred a small but significant survival advantage over radiotherapy alone in NSCLC [94]. Concomitant cetuximab and radiotherapy prolonged the survival of patients with locally advanced squamous cell carcinoma of the head and neck better than radiotherapy alone [95].…”
Section: Cetuximab and Radiotherapymentioning
confidence: 99%